2006
DOI: 10.1111/j.1439-0418.2006.01078.x
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of the diamondback moth (Plutella xylostella L.) and its parasitoids in Ethiopia: influence of geographical region and agronomic traits

Abstract: Surveys were carried out in 2001 in brassica-producing areas of Ethiopia to determine the geographic distribution and severity of diamondback moth (DBM) and occurrence of indigenous parasitoids. Principal component analysis was used to analyse the importance of nine parameters -DBM density, parasitism by different parasitoid species (Oomyzus sokolowskii, Diadegma spp., Apanteles sp. and overall parasitism), cropping systems, pesticide use, frequency of pesticide application and altitude. A total of 194 brassic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Until the early 1960s when large scale application of synthetic insecticides was introduced to commercial vegetable farming, P. xylostella was not a major pest in China [43]. The use of pesticides that are harmful to the third trophic level need to be minimised in favour of less harmful plant protection compounds to allow biological control to play a role in integrated pest management [44]. In particular, an active natural enemy fauna can reduce the frequency with which insecticides applications are required and kill survivors of insecticide application to prevent the development of resistance in the pest population.…”
Section: Discussionmentioning
confidence: 99%
“…Until the early 1960s when large scale application of synthetic insecticides was introduced to commercial vegetable farming, P. xylostella was not a major pest in China [43]. The use of pesticides that are harmful to the third trophic level need to be minimised in favour of less harmful plant protection compounds to allow biological control to play a role in integrated pest management [44]. In particular, an active natural enemy fauna can reduce the frequency with which insecticides applications are required and kill survivors of insecticide application to prevent the development of resistance in the pest population.…”
Section: Discussionmentioning
confidence: 99%
“…Low numbers of O. sokolowskii in south-western Ethiopia were attributed to probable competition with Apanteles sp. (Ayalew and Go, 2006). Similarly, Liu et al (2000) reported a negative relationship in parasitism level between O. sokolowskii and C. vestalis, which could explain partly that parasitism due to C. vestalis was greater during the second part of dry season.…”
Section: Discussionmentioning
confidence: 86%
“…In the present study, high interfield variability of parasitism rates (0e50%) indicates that crop management, especially insecticide use, but possibly also landscape context, eg semi-natural habitats or crops providing food or alternative hosts to parasitoids, could influence biocontrol by natural enemies (Bianchi et al, 2008). Surveys conducted in 2001 in brassica-producing areas of Ethiopia (194 brassica fields, 13 areas) revealed high variability among areas, with overall parasitism ranging from 3.6 to 79.5% (Ayalew and Go, 2006). Parasitism by indigenous parasitoid species was low (13.2%) and DBM density was high in the Rift Valley, the major brassica-producing area.…”
Section: Discussionmentioning
confidence: 87%
“…Recent and conservative estimates show that the total annual costs associated with the worldwide management of P. xylostella are approximately US$ 4 billion (Zalucki et al , ). Among the reasons usually mentioned to explain the high incidence of diamondback moth are the absence of effective natural enemies, as well as its high reproductive potential and ability to rapidly develop resistance to insecticides (Lim, ; Talekar & Shelton, ; Ayalew & Ogol, ; Ayalew et al , ; Furlong et al , ; Sayed & Teilep, ). Combination of these factors has hampered the control of P. xylostella , making the economical production of brassicas impracticable in certain regions of the world (Sarfraz et al , ).…”
Section: Introductionmentioning
confidence: 99%